THE EFFECT OF FIRM SIZE, LEVERAGE, AND PROFITABILITY ON FIRM VALUE WITH SYSTEMIC RISK AS A MODERATING VARIABLE IN BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE DURING 2021-2025 - Heri Susanto; Hari Gursida; Retno Martanti Endah L (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
This study aims to examine the effect of firm size, leverage, and profitability on firm value with systemic risk as a moderating variable in banking companies listed on the Indonesia Stock Exchange during the 2021–2025 period. The research employed a quantitative approach using panel data, combining time-series and cross-sectional data. Panel data regression with the Moderated Regression Analysis (MRA) approach was applied to analyze the relationships among variables. The findings indicate that firm size has a positive but insignificant effect on firm value, implying that asset scale is no longer the primary consideration for investors in assessing banking firms. Leverage shows a negative and significant effect on firm value, indicating that high debt levels increase investors’ perceptions of financial risk. Profitability demonstrates a relatively weak influence on firm value in the baseline model. However, after systemic risk is incorporated as a moderating variable, the relationships among variables become more dynamic and significant. Systemic risk strengthens the effect of profitability and mitigates the negative impact of leverage on firm value, while weakening the influence of firm size. These results confirm that firm value in the modern banking industry is determined not only by internal financial fundamentals but also by external conditions and financial system stability. Therefore, banking companies need adaptive strategies through effective risk management, operational efficiency, and stronger resilience to systemic pressures in order to enhance firm value sustainably